Oral kallidinogenase improved visual acuity and maintained chorioretinal blood flow levels after treatment for diabetic macular edema - Tsuiki E (Dove Medical Press, 2018)
Eiko Tsuiki,1 Kiyoshi Suzuma,2 Makiko Matsumoto,1 Yasser Helmy Mohamed,1 Takashi Kitaoka1 1Department of Ophthalmology and Visual Sciences, Graduate School of Biomedical Sciences, Nagasaki University, Nagasaki, Japan; 2Department of Ophthalmology and Visual Sciences, Kyoto University Graduate School of Medicine, Kyoto, Japan Purpose: This study was designed to investigate the therapeutic effects of oral kallidinogenase medication as an adjuvant therapy in treating patients with diabetic macular edema (DME). Study design: This was a prospective, open-labeled, randomized study. Methods: All patients were given posterior sub-Tenon triamcinolone acetonide (STTA) injection and focal laser treatment session for DME. The patients were subdivided into two groups: 1) those treated with oral kallidinogenase for at least 6 months after local treatment (treated group) and 2) those treated without oral kallidinogenase (untreated group). In this study, best-corrected visual acuity (BCVA), central retinal thickness (CRT), subfoveal choroidal thickness (SCT), and chorioretinal blood flow level were measured in 17 patients (19 eyes). Chorioretinal blood flow levels at the disc and macula were measured by laser speckle flowgraphy and evaluated using the mean blur rate (MBR). These data were measured at baseline and at 1, 3, and 6 months after treatment initiation. Results: BCVA at 6 months after treatment significantly improved in treated group (P<0.05). But the mean CRT after treatment significantly decreased in both groups. There was no significant difference in the mean SCT at baseline between the two groups. The mean SCT after treatment in treated group was significantly thinner than that before treatment (P<0.05). Compared to baseline (100%), MBR at the disc and the macula at 6 months after treatment significantly decreased to 84.8% and 86.2%, respectively, in untreated group (P<0.05), though it remained unchanged at 98.7% and 99.7% in treated group. Conclusion: Oral kallidinogenase medication is useful as an adjuvant therapy to enhance the therapeutic effect of STTA in DME patients. Keywords: kallidinogenase, diabetic macular edema, laser speckle flowgraphy, enhanced depth imaging optical coherence tomography